Application of machine learning in restoration of dental defect - WANG Yue, LI Hangyun, TANG Wanyi, WU Junhua (Editorial Office of Stomatology, 2024)
As an important branch of artificial intelligence, machine learning meets the demand for digital intelligence in prosthodontics with the rapid development and application of its algorithm. This review provides an overview of the application of machine learning algorithms in dental restoration, including the design of dental prostheses, tooth shade selection, and tooth preparation line detection. Additionally, this paper also briefly analyzes the merits of machine learning and discusses the challenges and issues in current research, to provide references for research on machine learning algorithms in prosthodontics.